The Leadership Planning and Education Quality of Salafi Islamic Boarding Schools - Syihabudin, Tubagus; Syafuri, B; Fauzi, Anis (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Salafiyah Islamic boarding schools aim to teach and practice the Al-Qur'an and Al-Hadith based on understanding the best generation. The issue of leadership regeneration and education quality is the weakness of Salafi Islamic boarding schools (IBS) because it is carried out suddenly and seems to lack attention. Integrating these educational goals requires leadership and quality based on planning so they can compete equally with other educational institutions. The research aims to analyse leadership planning in achieving Salafi IBS. The research method uses qualitative with a grounded theory approach at the Salafiyah At-Thahiriiyah IBS in Serang City and data collection by interviews and literature study. The research results show leadership planning and quality of education in Salafiyah IBS through increased leadership training, scientific capacity and education quality standards in Salafiyah IBS. There is a strengthening in the leadership planning of Salafiyah IBS through gradual leadership regeneration. The implications of research by strengthening leadership planning on the quality of education can use a design thinking approach that will help solve internal problems through leadership training, scientific capacity, gradual regeneration and education quality standards in Salafiyah IBS.